Analysis of Organizational Climate, Work Motivation on Employee Performance Mediated by Organizational Citizenship Behavior in The Work Unit of National Narcotics Agency North Sumatra Province - Mariani Valentina Tampubolon; Wilchan Robain; Kiki Farida Ferine (Yayasan Multidimensi Kreatif, 2024)
The objective of this research was to examine and evaluate the impact of work motivation and organizational climate on employee performance, as well as the role that organizational citizenship behavior plays in mediating these relationships in Work Unit of BNN North Sumatra Province. This was a descriptive quantitative study with a 56-person research sample. Structural Equation Modeling, or SEM, was used to evaluate the data. Overall, the study's discussion and results lead to the conclusion that organizational atmosphere has a considerable and favorable impact on worker performance. In Work Unit of BNN North Sumatra Province, organizational atmosphere and work motivation on employee performance can be mediated by organizational citizenship behavior characteristics, which have a positive and significant influence on employee performance.